Clinical Meaningfulness of the Changes in Muscle Performance and Physical Function Associated With Testosterone Administration in Older Men With Mobility Limitation - Travison, Thomas G. (Oxford University Press, 2011)
CONTEXT. Testosterone in Older Men with Mobility Limitations Trial determined the effects of testosterone on muscle performance and physical function in older men with mobility limitation. Trial’s Data and Safety Monitoring Board recommended enrollment cessation due to increased frequency of adverse events in testosterone arm. The changes in muscle performance and physical function were evaluated in relation to participant’s perception of change. METHODS. Men aged 65 years and older, with mobility limitation, total testosterone 100–350 ng/dL, or free testosterone less than 50 pg/mL, were randomized to placebo or 10 g testosterone gel daily for 6 months. Primary outcome was leg-press strength. Secondary outcomes included chest-press strength, stair-climb, 40-m walk, muscle mass, physical activity, self-reported function, and fatigue. Proportions of participants exceeding minimally important difference in study arms were compared. RESULTS. Of 209 randomized participants, 165 had follow-up efficacy measures. Mean (SD) age was 74 (5.4) years and short physical performance battery score 7.7 (1.4). Testosterone arm exhibited greater improvements in leg-press strength, chest-press strength and power, and loaded stair-climb than placebo. Compared with placebo, significantly greater proportion of men receiving testosterone improved their leg-press and chest-press strengths (43% vs 18%, p = .01) and stair-climbing power (28% vs 10%, p = .03) more than minimally important difference. Increases in leg-press strength and stair-climbing power were associated with changes in testosterone levels and muscle mass. Physical activity, walking speed, self-reported function, and fatigue did not change. CONCLUSIONS. Testosterone administration in older men with mobility limitation was associated with patient-important improvements in muscle strength and stair-climbing power. Improvements in muscle strength and only some physical function measures should be weighed against the risk of adverse events in this population.